A weakly-interacting many-body system of Rydberg polaritons based on electromagnetically induced transparency - Bongjune Kim (Nature Portfolio, 2021)
Rydberg-state atoms are characterized by significant dipole–dipole interaction making them useful for quantum information applications. The authors present experimental results on a high-optical-depth electromagnetically-induced-transparency medium of weakly interacting Rydberg atoms as a way of realizing Bose–Einstein condensates of polaritons.